Casimir Forces between a Dielectric and Metal: Compensation of the Electrostatic Interaction - Vitaly B. Svetovoy (Physics, 2023)
The Casimir forces between metals or good conductors have been checked experimentally. Semiconductors and especially dielectrics have not been investigated because of the surface charges, which generate strong electrostatic forces. Here, it is proposed to study the Casimir interaction of a dielectric and metal using a thin dielectric layer deposited on an optically thick metallic substrate. If the thickness of the layer is a few tens of nanometers, the electrostatic force due to charging can be compensated for by applying an extra voltage between the metallic plates. On the other hand, the contribution of the dielectric layer to the Casimir force is sufficiently large to extract information about the interaction between the bulk dielectric and metal.